Meta-synthesis of qualitative research on return to work among employees with common mental disorders - Andersen, Malene F.; Nielsen, Karina M.; Brinkmann, Svend (Scandinavian Journal of Work, Environment & Health, 2012)
' ' OBJECTIVES ': 'The purpose of this study was to investigate which opportunities and obstacles employees with common mental disorders (CMD) experience in relation to return to work (RTW) and how they perceive the process of returning to work. In addition, the study explores what characterizes an optimal RTW intervention and points to possible ways to improve future interventions for employees with CMD. ' ' METHODS ': 'A systematic literature search was conducted, and eight qualitative studies of medium or high quality published between 1995–2011 were included in this systematic review. The eight studies were synthesized using the meta-ethnographic method. ' ' RESULTS ': 'This meta-synthesis found that employees with CMD identify a number of obstacles to and facilitators of returning to work related to their own personality, social support at the workplace, and the social and rehabilitation systems. The employees found it difficult to decide when they were ready to resume work and experienced difficulties implementing RTW solutions at the workplace. ' ' CONCLUSIONS ': 'This study reveals that the RTW process should be seen as a continuous and coherent one where experiences of the past and present and anticipation of the future are dynamically interrelated and affect the success or failure of RTW. The meta-synthesis also illuminates insufficient coordination between the social and rehabilitation systems and suggests how an optimal RTW intervention could be designed.
Keywords: back to work; common mental disorder; mental disorder; mental health; mental illness; meta-ethnography; meta-synthesis; qualitative research; rehabilitation; return to work; review; RTW; sick leave; social support; work accommodation